2010
DOI: 10.1103/physrevd.81.035014
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence between domain walls and “noncommutative” two-sheeted spacetimes: Model-independent matter swapping between branes

Abstract: It is shown that a two-brane world made of two domain walls can be seen as a noncommutative two-sheeted spacetime under certain assumptions. This equivalence implies a model-independent phenomenology: Matter swapping between the two 3-branes (or sheets) is predicted through fermionic oscillations induced by magnetic vector potentials. This phenomenon, which might be experimentally studied, could reveal the existence of extra dimensions in a new and very affordable way.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
134
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 32 publications
(134 citation statements)
references
References 76 publications
0
134
0
Order By: Relevance
“…In the present work we discuss the possibility that an astrophysical magnetic vector potential could lead to such a matter 1 The model used in the present work can be proved and derived [15] from a domain wall approach in which the Dvali-Gabadadze-Shifman mechanism [23] is responsible for the gauge field localization on the brane. This mechanism allows electric charge leaks [23] contrary to other models, such as the bubble brane approach [3] for instance.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…In the present work we discuss the possibility that an astrophysical magnetic vector potential could lead to such a matter 1 The model used in the present work can be proved and derived [15] from a domain wall approach in which the Dvali-Gabadadze-Shifman mechanism [23] is responsible for the gauge field localization on the brane. This mechanism allows electric charge leaks [23] contrary to other models, such as the bubble brane approach [3] for instance.…”
Section: Introductionmentioning
confidence: 89%
“…Testing the existence of branes or extra dimensions is therefore becoming a fundamental challenge. Such evidences are expected to be obtained through high energy collisions [2][3][4], but it has been also demonstrated that some detectable effects could also be observed at low energy [2,3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . This is the topic of the present paper.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations